Peningkatan Publikasi Ilmiah Melalui Pelatihan Penulisan Artikel Ilmiah Bagi Mahasiswa - Prihatin, Yulianah; Arisni Kholifatu A.S; Resdianto Permata R (BALE LITERASI, 2021)
This service activity aims to provide understanding and knowledge to students about writing scientific articles so that they can improve scientific publications. This activity is not only carried out by providing theories about writing scientific articles, but also coaching clinic activities as a form of training for students. The implementation method is carried out online or online through zoom media. The presentation of the material was given directly by the resource person to partner students, then students were given one week to apply the material obtained through the coaching clinic. The coaching clinic is carried out with the aim of maximizing monitoring of students during the practice of writing articles.